LOGO AZKO DALAM PERSPEKTIF SEMIOTIKA ROLAND BARTHES: KONSTRUKSI IDENTITAS VISUAL MELALUI REBRANDING: AZKO Logo in the Perspective of Roland Barthes’ Semiotics: Constructing Visual Identity through Rebranding - Harris Effendi; Ekananda Haryadi (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2025)
AZKO Logo in the Perspective of Roland Barthes’ Semiotics: Constructing Visual Identity through Rebranding. This study examines the AZKO logo through Roland Barthes’ semiotic framework, focusing on three layers of meaning: denotation, connotation, and myth. Using a qualitative approach, the analysis explores visual elements capital, which are letters “AZ” and “KO,” the red dot, and the dominant use of red that constructs meanings beyond their graphic form. Findings reveal that the logo functions not only as a visual identity but also as a symbolic medium representing completeness, collaboration, openness, and adaptability. The rebranding from Ace Hardware Indonesia to AZKO illustrates a strategic shift that communicates efficiency, courage, and professionalism, while producing myths of modernity and local independence. Academically, this research contributes to visual semiotics by highlighting logos as ideological communication tools. Practically, it provides insights for companies seeking to reinforce local identity through rebranding. Future research is encouraged to explore culture-based logo designs, conduct global-local rebranding comparisons, and investigate consumer perception to better understand public interpretations.